ANALISA SEMIOTIKA SOSIAL VISUAL PADA IKLAN DENIM DIESEL “BE STUPID” - Sophia Purbasari (ArtComm, 2021)
Visual communication, especially advertising, must be multi-faceted and multidimensional in order to gain positive attention and response from the community. The ads must have a visual narrative composed of visual elements having their own meaning and forming the overall meaning for the visual narrative, both verbal or non-verbal. Visual narrative structure of the ads can be described and exposed through the decomposition of visual social semiotic interpretation seen from the relationship of visual elements in it so that it can be understood how the meaning is formed and the communication process between the messenger is the creator of the ad and the audience can happen. The objectives of the study were to analyze the embedded meanings of visual images in Diesel print ads campaign: “Be Stupid”. The approach of this study was a qualitative descriptive one by using grounded theory method. The visual social semiotic analyzed by using the descriptive framework of visual grammar proposed by Kress and Leeuwen (2006). This study revealed that the visual images embedded three visual meanings, namely representation, interactive and composition meaning, and the analysis of the visual messages.The result of this research are.